Difficulties In Employing Paragraph Response Theory In Educational And Psychological Sciences From The Point Of View Of Graduate (Journal of the College of Basic Education, 2024)
The current research seeks to identify the difficulties of employing paragraph response theory in educational and psychological sciences from the point of view of graduate students. In order to achieve the objectives of the current research, the researcher adopted the descriptive analytical method as an approach to the current study through a sample of graduate students specializing in measurement and evaluation, amounting to (100) male and female students. In order to collect data, a questionnaire was prepared to measure the variables of the current research, and after verifying the validity and reliability of the questionnaire, the study concluded. The assumptions of the item response theory are unrealistic, and the pillars of the item response theory are largely incomplete, in addition to difficulties related to the nature of the programs used in the study. However, despite this, measurement students and specialists find this theory very effective and vital in analyzing data.